Innovative approaches, practices, and strategies in adult education - Tomlin, Antione D. (Emerald Publishing Limited, 2025)
"To be better, we must do better! As educators and practitioners, it is our responsibility to do right by our students, no excuses!"Antione D. Tomlin, PhD As higher education continues to evolve, institutions are reimagining how they serve adult learners--students who bring diverse experiences, responsibilities, and aspirations to the classroom. Innovative Approaches, Practices, and Strategies in Adult Education explores the transformative strategies, innovative pedagogies, and institutional shifts that enhance adult learner success while addressing the evolving challenges educators face today. Through a lens of equity, flexibility, and student-centered innovation, this collection delves into three critical themes: redefining success through assessment, which examines how multiple measures assessments provide a more holistic understanding of student potential beyond standardized testing; supporting diverse learners, which highlights initiatives that create inclusive learning environments for first-generation, international, and adult students; and promoting flexibility and innovation, showcasing adaptive pedagogical strategies, online learning innovations, and organizational transformation to meet the unique needs of adult learners. With contributions from leading scholars and practitioners, this book offers actionable insights and evidence-based strategies that empower educators to drive meaningful change. It is a call to action for institutions to embrace innovation, cultivate equity, and prioritize student success, ensuring a more accessible and transformative future for adult learners in higher education.
Includes index.
Keywords: Adult education.; Education -- Adult & Continuing Education.; Adult education, continuous learning.; elektronické knihy; electronic books